Los Medeiros: uma família de artistas cearenses - Medeiros, Camile Leal de (2023)
This is a research that deals with the creative process of writing a script for a documentary about a family of artists from Ceará that I belong to, the self-titled Los Medeiros. In it, I focus on gathering part of the collection of images and documents from these artists as a procedure to create other poetic materials, aiming to use them as inspiration for the creation and production of a script for a documentary. Bearing in mind that several artists from Fortaleza end up being forgotten over time, this research intends to contribute to the memory of the history of these artists, also giving visibility to their trajectories. Among the objectives of the research are to record my creation process, to gather new poetic materials, to create the script for the documentary, to reflect on the ways of thinking about art, the freedom of creation and the fluidity with which this occurs. For this, a bibliographical survey was carried out (Salles, Agamben, Kastrup, Didi-Hubermann, Vilain, Comolli, and others), selection of documentary material, video interviews, field diary, fictional reports and creation of boards with some collected images, bringing a contribution to research in the arts, both for the relationships between the chosen authors, and for the inspirations they provided me for writing the script.